Identity integration and family ethnic socialization as moderators of acculturation stress and psychological outcomes - Johansen, Samantha van Limbeek, author; Le, Thao N., advisor; MacPhee, David, committee member; Swaim, Randall, committee member (Colorado State University. Libraries, 2011)
Acculturation stress is the stress associated with navigating between the dominant culture and one's culture of origin. This stress can be particularly daunting for young people as they are also grappling with issues of identity. For some, the stress can pose a risk for poor psychological outcomes such as depression and anxiety (Choi et al., 2008; Suarez-Morales & Lopez, 2009). As societies like the United States become more ethnically, culturally, and linguistically diverse (American Psychological Association, 2003), multiculturalism and acculturation become increasingly important areas to study. Although it can be straining, research suggests that individuals living among multiple cultures benefit, in terms of positive psychological outcomes, if they are able to develop a bicultural or multicultural identity (Bacallao & Smokowski, 2009; Suarez-Orozco & Suarez-Orozco, 2001). Studies have also highlighted the importance of family factors such as support and solidarity in terms of facilitating positive psychological outcomes (Bacallao & Smokowski, 2005; Choi et al., 2007; Rivera, 2007). The current study uses an existing multisite data set, the Multiple University Survey on Identity and Culture (MUSIC) data set (2008). The survey targeted all undergraduate students at multiple universities across the United States and included individuals between ages 17-25 (N=10,572). For the purpose of this study, only individuals who indicated 1st generation or 2nd generation immigrant status were included (N= 3,654). Multivariate statistical analyses were then conducted in terms of multiple regressions. An integrated bicultural identity was a significant moderator of acculturation stress and psychological well-being, as was family ethnic socialization (FES). This indicates that individuals who have resolved identities and are low on conflict are more likely to have higher levels of psychological well-being in the face of acculturation stress. In turn, individuals whose families engage in more FES are more likely to have higher levels of psychological well-being in the face of acculturation stress. FES, however did not moderate the relationship between acculturation stress and maladaptive psychological outcomes such as depression and social anxiety. Bicultural identity distance and ethnic identity resolution were significant moderators of depression and social anxiety (respectively) in the face of acculturation stress. It is becoming clearer, in the field of human development, that addressing youth risk factors and vulnerabilities does not necessarily mean that we are finding ways to promote positive youth outcomes. What this study highlights is the notion that one can still find ways to promote well-being in the face of acculturation stress even though vulnerabilities to maladaptive outcomes have not been entirely eliminated.
Keywords: emerging adulthood; acculturative stress; family ethnic socialization; identity; psychological well-being